Investment in forests: What role for community forestry in Nepal? - Adhikary, Anukram (2019)
Forest management in Nepal until the mid-1970s was characterized by systems that helped to reinforce the power of the state over forest resources. It wasn’t until the early 1990s that strong political will was shown by the elected leaders to support the tenure rights devolution agenda. With it, strong legal foundations for community-based forest management were introduced. Today, Nepal's Community Forestry (CF) is widely regarded as an archetypal model for halting deforestation and forest degradation. At present, the scope of CF activities has substantially widened from its early focus on forest protection and subsistence use to a more integrated approach to accommodate wider social and economic objectives including leadership development at the local levels. In recent years, the Community Forest User Groups (CFUGs) have been using their proprietary rights to attract investment to help spawn a variety of community forest enterprises (CFEs), including timber processing, tourism activities, and small firms that process, produce and market non-timber forest products. Against this backdrop, this paper examines what role CF can or should play to manage these new responsibilities. Literature review, interviews with twelve CFE operators, and consultations with relevant actors and policy makers across Nepal were conducted for the purpose of this study. It was found that CFEs adopt varied modalities of management. Most are managed by a single CFUG whilst others are borne through a partnership agreement between two or more CFUGs, or function through a partnership with a private entity. Investment in the form of capital support and skilled labor is found to be made by the CFUGs themselves in majority of the cases. Nevertheless, investment by the government and various donor-funded projects in fixed assets such as machineries and equipment along with capacity development cannot be overlooked. However, the poor performance of these CFEs in Nepal with most of them operating in loss suggests that there are drawbacks in the manner in which they are currently being managed and operated. Furthermore, lack of start-up capital is cited as one of the major barriers to establishment of such enterprises. Another common constraint was the lack of adequate capital to sustain the enterprises without external support. Tenure rights devolution in the form of CF in Nepal has created and attracted investment in CFEs. CFEs, however, face serious challenges related to financial viability and performance. Hence, analyses of prevailing investments in the CFEs can help to better understand how to overcome investment barriers in Nepal and thereby, boost community investment in the forests in Nepal.